Fighting Search Engine Amnesia: Reranking Repeated Results - Shokouhi, Milad; White, Ryen W.; Bennett, Paul; Radlinski, Filip (Proceedings of the 36th Annual ACM SIGIR Conference (SIGIR 2013), 2013)
Web search engines frequently show the same documents repeatedly for different queries within the same search session, in essence forgetting when the same documents were already shown to users. Depending on previous user interaction with the repeated results, and the details of the session, we show that sometimes the repeated results should be promoted, while some other times they should be demoted. Analysing search logs from two different commercial search engines, we find that results are repeated in about 40% of multi-query search sessions, and that users engage differently with repeats than with results shown for the first time. We demonstrate how statistics about result repetition within search sessions can be incorporated into ranking for personalizing search results. Our results on query logs of two large-scale commercial search engines suggest that we successfully promote documents that are more likely to be clicked by the user in the future while maintaining performance over standard measures of non-personalized relevance.